1980
DOI: 10.1080/09553008014550321
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Irradiated Glia and Glioma Cells Studied with a New Cloning Technique

Abstract: A method allowing cloning of monolayer cultured cells with a low plating efficiency was developed. Cells were grown in several small palladium squares to obtain a high cell density. These squares were surrounded by non-adhesive agarose to prevent large distance migration and thereby mixing of the clones. By using easily-cloned hamster cells for comparison it was found that the survival curves were similar to the curves obtained with conventional cloning. The new method was used to compare the radiosensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The human melanoma line C-32, however, is significantly more radioresistant than other tumour lines we have examined. Other investigators have reported some human glioblastoma lines to be radioresistant in vitro, though the frequency of radioresistant cells in vivo is unknown (Gerwick et al, 1977;Nilsson et al, 1980). Inherent cellular radioresistance may thus, in some cases, be an important factor in clinical radiocurability, though results from several laboratories with a wide variety of human tumour lines have shown few apart from the C-32 melanoma, to be unusually radioresistant in vitro (Smith et al, 1978;Weininger et al, 1978;Wells et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The human melanoma line C-32, however, is significantly more radioresistant than other tumour lines we have examined. Other investigators have reported some human glioblastoma lines to be radioresistant in vitro, though the frequency of radioresistant cells in vivo is unknown (Gerwick et al, 1977;Nilsson et al, 1980). Inherent cellular radioresistance may thus, in some cases, be an important factor in clinical radiocurability, though results from several laboratories with a wide variety of human tumour lines have shown few apart from the C-32 melanoma, to be unusually radioresistant in vitro (Smith et al, 1978;Weininger et al, 1978;Wells et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The poor results must instead have other explanations, such as a low 'intrinsic' radiosensitivity of the glioma cells [10,11,20,21], presence of hypoxic cells (see review by Hill [22]) or failure to include all tumor cells in the irradiated volume. It is possible that combinations of factors, rather than a single cause, explain the poor treatment of results for patients with malignant gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Nederman et al [9] on the effects of betamethasone was very limited while the study by Millar et al [10] on dexamethasone was carried out in more detail. Cultured glioma cells are known to have a low cloning efficiency [10,11] and it is therefore difficult to clone them according to the original description by Puck and Marcus [12]. An alternative method to obtain radiation survival parameters is to use the extrapolation method, which has been previously described to be a reliable and easily handled method [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petri dishes are layered with a thin film of agarose, anda pattern of 0.3 mm diameter palladium islands are deposited onto the agarose. Cells are unable to grow on agarose but grow on the islands to form colonies [26].…”
Section: Tumor Heterogeneitymentioning
confidence: 99%